The Biomechanical Response of the Cornea in Orthokeratology - Wu, Jinfang; Fang, Wenxuan; Xu, Huiwen; Liu, Xiaode; Zhao, Dongliang; Rong, Qiguo (Frontiers in Bioengineering and Biotechnology, 2021)
Orthokeratology has been widely used to control myopia, but the mechanism is still unknown. To further investigate the underlying mechanism of corneal reshaping using Orthokeratology lenses via the finite element method, numerical models with different corneal curvatures, corneal thicknesses, and myopia reduction degrees had been developed and validated to simulate the corneal response and quantify the changes in maximum stress in the central and peripheral corneal areas during Orthokeratology. The influence of the factors on corneal response had been analyzed by using median quantile regression. Partial eta squared in analysis of variance models were established to compare the effect size of these factors. The results showed central and peripheral corneal stress responses changed significantly with increased myopia reduction, corneal curvature, and corneal thickness. The target myopia reduction had the greatest effect on the central corneal stress value (partial eta square = 0.9382), followed by corneal curvature (partial eta square = 0.5650) and corneal thickness (partial eta square = 0.175). The corneal curvature had the greatest effect on the peripheral corneal stress value (partial eta square = 0.5220), followed by myopia reduction (partial eta square = 0.2375) and corneal thickness (partial eta square = 0.172). In summary, the biomechanical response of the cornea varies significantly with the change in corneal conditions and lens designs. Therefore, the orthokeratology lens design and the lens fitting process should be taken into consideration in clinical practice, especially for patients with high myopia and steep corneas.